Catholics and millennialism: a theo-linguistic guide - Kappeler, Warren (American university studies / 7, 2017)
Rhetorical controversies within Catholic Eschata -- Exploring the intertextuality of millenarianism & Catholicism -- Theology as theodicy: millennial rhetoric in church history -- Millennial trends in modern culture -- Catholic fundamentalism, dissent, & pre-millenarian Catholics -- Post-millennialism, liberal Catholics, & social progress -- Catholic realism & Augustinian anti-millennialism -- Kingdom ethics as a modality of Catholic discourse